Introduction of an energy efficiency tool for small scale biomass gasifiers – A thermodynamic approach. (1st January 2017) - Vakalis, S.; Patuzzi, F.; Baratieri, M.
Graphical abstract: Highlights: Analysis of plants for electricity, heat and materials production. Thermodynamic analysis by using exergy, entransy and statistical entropy. Extrapolation of a single efficiency index by combining the thermodynamic parameters. Application of methodology for two monitored small scale gasifiers. Abstract: Modern gasification plants, should be treated as poly-generation facilities because, alongside the production of electricity and heat, valuable or waste materials streams are generated. Thus, integrated methods should be introduced in order to account for the full range and the nature of the products. Application of conventional hybrid indicators that convert the output into monetary units or CO2 equivalents are a source of bias because of the inconsistency of the conversion factors and unreliability of the available data. Therefore, this study introduces a novel thermodynamic-based method for assessing gasification plants performance by means of exergy, entransy and statistical entropy. A monitoring campaign has been implemented on two small scale gasifiers and the results have been applied on the proposed method. The energy plants are compared in respect to their individual thermodynamic parameters for energy production and materials distribution. In addition, the method returns one single value which is a resultant of all the investigated parameters and is a characteristic value of the overall performance of an energy plant.